2004
DOI: 10.1074/jbc.m402439200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Interaction and Dimerization of Eukaryotic SMC Hinge Domains

Abstract: The eukaryotic SMC1/SMC3 heterodimer is essential for sister chromatid cohesion and acts in DNA repair and recombination. Dimerization depends on the central hinge domain present in all SMC proteins, which is flanked at each side by extended coiled-coil regions that terminate in specific globular domains. Here we report on DNA interactions of the eukaryotic, heterodimeric SMC1/SMC3 hinge regions, using the two known isoforms, SMC1␣/SMC3 and the meiotic SMC1␤/SMC3. Both dimers bind DNA with a preference for dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 46 publications
(72 reference statements)
6
67
0
Order By: Relevance
“…While DNA binding studies have shown that SMC proteins can directly bind to DNA (Akhmedov et al, 1998;Akhmedov et al, 1999;Chiu et al, 2004), similar studies have not been performed for the klesin subunits. Therefore, it is generally thought that the SMC proteins are responsible for cohesin complex binding to the chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…While DNA binding studies have shown that SMC proteins can directly bind to DNA (Akhmedov et al, 1998;Akhmedov et al, 1999;Chiu et al, 2004), similar studies have not been performed for the klesin subunits. Therefore, it is generally thought that the SMC proteins are responsible for cohesin complex binding to the chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis of glycine residues within Smc1 and Smc3 at sites predicted to lie at the interface between their hinge dimerization domains destroys their interaction in vitro. Because of the dimeric hinge's doughnut-shaped structure, there exist two independent interaction surfaces, and interestingly, mutation of both is required to abolish their interaction, at least in vitro (Chiu et al 2004). The effect of mutations that specifically disrupt the two interaction surfaces have not yet been investigated in vivo.…”
Section: How Might Cohesin Hold Sister Chromatids Together?mentioning
confidence: 99%
“…The joint requirement for these two domains is even more surprising given their apparent physical separation (;40 nm) based upon electron micrographs of cohesin [13]. Interestingly, in vitro analyses of bacterial Smc complexes have implicated the hinge domain in single-stranded and double-stranded DNA binding [37,44] and DNA-dependent stimulation of the ATPase activity of the head [44]. Thus, our in vivo study combined with these in vitro studies support DNA-dependent functional interactions between the opposite ends of Smc complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, site-directed mutagenesis of conserved Smc1 residues in the Hinge, Walker A, Walker B, and Signature motifs demonstrated that Smc1 must bind Mcd1 and Smc3, as well as bind and hydrolyze ATP in order for cohesin to bind chromatin [7,21,22,37]. While informative, these mutational analyses of cohesin-chromatin association leave key questions unanswered.…”
Section: Introductionmentioning
confidence: 99%